Riemman solitions in para sasakian Manifolds admitting different semi-symmetric structures - Raghujyoti Kundu; Ashoke Das; Ranjit Saibya; Ashis Biswas (Journal of Hyperstructures, 2023)
The object of the present paper is to study the Rie-mannian solitons on para sasakian manifolds admitting E.R=0, E.t P=0, E.E=0, E.P*=0, E.M=0, E.Wi=0, E.Wi*=0, R.R=0, R.P=0, R.E=0, R.P*=0, R.M=0, R.Wi=0, RWi*=0, R.K=0, R.C=0, E.C = 0, E.k=0, for i=1, 2, ..., 9.